2019
DOI: 10.2139/ssrn.3489866
|View full text |Cite
|
Sign up to set email alerts
|

Economic Growth, Institutional Quality and Financial Development in Middle-Income Countries

Abstract: The Working Paper Series seeks to disseminate original research in economics and finance. All papers have been anonymously refereed. By publishing these papers, the Banco de España aims to contribute to economic analysis and, in particular, to knowledge of the Spanish economy and its international environment. The opinions and analyses in the Working Paper Series are the responsibility of the authors and, therefore, do not necessarily coincide with those of the Banco de España or the Eurosystem. The Banco de E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
2
1
Order By: Relevance
“…This could have been caused by prevailing poor bureaucratic quality, quality of law and order and governance in these nations, which also affects the selection, monitoring and replacement process of the government and the government capacity to effectively implement policies post formulation. This result however contradicts Heras Recuero and Pascual González (2019) who concluded a positive effect of institutional quality on economic growth in middle income countries. Moreover, we introduced an interaction term between digital financial inclusion (DFII) and institutional quality ( INSTITUTIONS ) to test whether the impact of digital financial inclusion goes through institutional quality.…”
Section: Methodscontrasting
confidence: 72%
“…This could have been caused by prevailing poor bureaucratic quality, quality of law and order and governance in these nations, which also affects the selection, monitoring and replacement process of the government and the government capacity to effectively implement policies post formulation. This result however contradicts Heras Recuero and Pascual González (2019) who concluded a positive effect of institutional quality on economic growth in middle income countries. Moreover, we introduced an interaction term between digital financial inclusion (DFII) and institutional quality ( INSTITUTIONS ) to test whether the impact of digital financial inclusion goes through institutional quality.…”
Section: Methodscontrasting
confidence: 72%
“…For 29 emerging economies, (Nguyen et al, 2018) proved that institutional quality impacted positively on economic growth. This finds support in Recuero & González, (2019) for middle-income countries. In Nigeria, Olanrewaju et al, (2019) showed that all the institutional quality variables employed in the study Granger-caused growth without a feedback.…”
Section: Empirical Literaturementioning
confidence: 66%
“…Furthermore, the endogenous growth theory implicitly highlighted the influence of institutional quality (IQ) on growth (Recuero & Gonzalez, 2019). Thus, incorporating "IQ" into equation (3.14):…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…From the theoretical framework and (9) above, the empirical models for this study is derived from the endogenous growth approach, which throws light on the impact of endogenous variables like domestic credit to the public and private sectors on economic growth in an economy. Thus, the model for this study, adapted from Pagano (1993) and Recuero and Gonzalez (2019) is specified as…”
Section: Model Specificationmentioning
confidence: 99%